Localizing the Global Goals: The Impact of Domestic Human Rights Issues on Japanese EFL Students’ Engagement with the SDGs - Sheridan , Robert; Tanaka, Kathryn M. (Journal of NELTA, 2025)
In recent years, an increasing number of English as a Foreign Language (EFL) textbooks centered on the Sustainable Development Goals (SDGs) have been developed. However, many emphasize global issues, leading to ―SDGs burnout as students struggle to relate to the content meaningfully. This study investigates the effectiveness of integrating domestic and international human rights topics into SDGs-related materials to increase student engagement and shape perceptions of their country‘s role in addressing SDGs-related issues. Over a fifteen-week semester, 58 lower-intermediate EFL students in Japan designed and taught lessons using SDGs-related articles featuring local and global human rights themes. Pre- and poststudy questionnaires measured changes in students‘ attitudes toward Japan‘s role in addressing domestic and international SDGs-related issues, as well as their interest and connection to the materials. Results showed a statistically significant increase in interest and relatability when domestic issues were included. While perspectives on Japan‘s domestic role remained largely unchanged, possibly due to a ceiling eff ect, views on its international role increased slightly, although not significantly. Qualitative responses identified empathy, awareness, and exposure to diverse perspectives as key factors contributing to interest and relatability. These findings suggest integrating local and global content may sustain student engagement and mitigate SDGs burnout.